Factores de riesgo que determinan la prevalencia de rinofaringitis aguda en niños menores de 5 años que son atendidos en el centro de salud N.1 de la ciudad de Tulcán - Campués Yacelga, Mariuxi Gabriela (2019)
Worldwide, acute respiratory infections (ARIs) are the leading cause of medical consultations and morbidity. The Americas are not exempt from this situation, as according to data from the Pan American Health Organization (PAHO), these infections represent 30 to 50% of pediatric consultations and 3.40% of hospitalizations. It is estimated that, in most countries, children under 5 years of age experience 4 to 8 episodes of ARI per year. To advance control of this problem, the Pan American Health Organization (PAHO), the World Health Organization (WHO), and the United Nations Children's Fund (UNICEF) jointly developed the AJEPI (Integrated Care of Prevalent Childhood Illnesses) strategy, introduced in the Americas in early 1996. This strategy addresses the assessment, classification, and treatment of prevalent diseases affecting children under 5 years of age in developing nations, such as acute respiratory infections (ARIs), among others. These infections, which account for the third largest number of childhood deaths in the region and for more than half of deaths in children under 5 years of age in some countries, present with 8 episodes of rhinopharyngitis per year.